The Effect of Vaccination Decision in Disease Modelling through Simulation - Teoh, Shian Li; Jane, Labadin; Phang, Piau; Shapiee, Abd Rahman; Ling, Yeong Tyng (2015)
Infectious disease is one of the health issues that threatens the world population. The spread of infectious diseases can be controlled via vaccination program and self-isolation as suggested by the public health organization. The individuals’ incentives to take the control measures are depend on their fearfulness on the disease. This fearfulness or feeling of fear is associated with human behavior. Hence, the objective of this study is to incorporate human behavior in disease modeling. We also aimed to study the level of fearfulness in both subpopulations of receiving complete information and receiving incomplete information and its impact to the vaccination program. In this paper, a model is developed by using individualbased modelling approach to capture the human behavioral changes during disease outbreak. The analysis of the results presented the relationship between the fearfulness and the vaccination decision of the individual. Hence, the level of fearfulness needs to be examined in order to organize an effective vaccination program.